Tinjauan Fikih Islam Terhadap Undang-Undang Nomor 1 Tahun 1974 Tentang Talak - Bakry, Kasman; Sirajuddin, Sirajuddin; Musriwan, Musriwan; Ahmad Arfah Mansyah (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
This study aimed to determine the review of Islamic jurisprudence on Law No. 1 of 1974 concerning the stipulation of rules requiring divorce before the Religious Courts. The research method was descriptive qualitative research with library research techniques, which focuses on the study of manuscripts and texts, and uses normative and philosophical juridical approaches. The results of the study showed that even in Islamic jurisprudence, divorce can occur and be considered valid, anytime and anywhere, if the husband who handed down the divorce is mature, reasonable, and not under pressure or coercion. However, Law Number 1 of 1974 requires that a divorce be valid, and divorce must be filed and carried out in front of a religious court session. This requirement does not conflict with Islamic jurisprudence, even scholars agree on the witness of divorce.